Amplification of purine rich region from DOCK9 gene for triple helix study in keratoconus eye disease - Mohamad Saperi, Siti Munira (2017)
Triple helix are formed by binding a scientific triple helix forming oligonucleotides (TFO) with high affinity and specificity to purine rich region in the major groove of homopurine sequence in the double stranded DNA (Chan & Glazer, 1997). In vitro study shows that triple helix formation alter the double helical conformation of DNA and inhibit process transcription and replication in DNA. The aim of the study is to amplify the purine rich region in DOCK9 gene for triple helix study in Keratoconus (KC) eye disease. DOCK9 gene were discovered as a candidate gene for KC which responsible in cytokinesis of the cell (Bykhovskaya, Margines, & Rabinowitz, 2016). At first, the purine rich region was amplified using a pair of primer designed based on the sequence of DOCK9 gene region obtained from NCBI. PCR cycle then performed with an optimum annealing temperature at 51°C. Expected sizes of PCR products were successfully obtained through agarose gel electrophoresis. Direct sequencing were done to verify the sequence of this potential TFO target site. Through direct sequencing results and alignment, purine rich sites were successfully amplified and verified. These potential TFO binding sites might be useful for specific inhibition in gene expression.